ANALISIS KUALITAS PELAYANAN, KEPERCAYAAN DAN NILAI TERHADAP KEPUASAN PESERTA DIDIK PADA LEMBAGA PENDIDIKAN DAN KETERAMPILAN (LPK) DI BANJARMASIN. (Studi pada LPK Kharisma, LP3I dan Borneo Training Center) - Apriya Santi; Nuril Huda (Universitas Lambung Mangkurat, 2015)
The evaluation on service quality can develop trust and positive perspective on value to give satisfaction to the customers. The purpose of this study was determine and analyze the influence of service quality factor, trust factor, value factor on satisfaction. How the influence of service quality factor on trust factor and value factor, the influence of trust factor on value factor, the indirect influence of service quality factor on satisfaction through trust and through value. It used Purposive Sampling, there are 108 samples as respondents of all population in LPK Kharisma, LP3I and Borneo Training Center. The analysis technique used Structural Equation Modeling with Confirmatory Factor Analysis and Regression. The results showed that service quality factors have an effect on the level of satisfaction. but the trust and the value factors don’t have an effect on the level of satisfaction. Service quality factor have an effect on the trust and the value, which states that the trust factors have an effect on the value. There is an indirect influence of service quality factor on satisfaction through trust, but there isn’t an indirect influence of service quality factor on satisfaction through value.